Rasio Konversi Pakan, Pertumbuhan dan Kelulushidupan Ikan Lele (Clarias Sp.) yang Diberi Pelet Komersial dan Maggot BSF Black Soldier Fly (Hermetia Illucens) - I Kadek Alamsta Suarjuniarta; Pande Gde Sasmita Julyantoro; I Wayan Darya Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
The purpose of this study was to determine the feed conversion ratio, weight growth and survival rate of Catfish (Clarias sp.) fed with commercial feed and the black soldier fly larvae (Hermetia illucens). The study was conducted from February-March 2021 located at PT Bala Biotech Indonesia, Karangasem, Bali. This study used an experimental method with a completely randomized design consisting of 3 treatments and 3 repetitions. The treatment A used 100% commercial feed, treatment B used 50% commercial feed + 50% BSF larvae and the treatment C used 100% BSF larvae. The result showed that the fish survival was 33±2.89%, weight growth 35.0±1.89g and FCR 0.67 in the treatment A, while treatment B resulted in 35±5.00% of survival, weight growth 33.6±0.85g and FCR 0.82, treatment C had 47±2.89% survival 18.7±1.89 g weight growth and FCR 1.12. The water quality parameters measured such as DO was ranged at 6.6-7.4 mg/l, temperature 25.8-25.9 oC, pH 6.9-7.0, ammonia level 0.7-1.4 mg/l, nitrite level 0.1-0.6 mg/l and nitrate level 3.0-5.3 mg/l. This study concluded that fish fed with 100% maggot BSF resulted in highest fish survival but the fish growth was lower compared to other treatments. Finally FCR in all treatments were not significantly different (P>0.05).